Open-access electronic diary for motor fluctuation and dyskinesia evaluation in aprkinson disease: comparison with paper diary - Terroba Chambi, Cinthia (2018)
Fil: Terroba Chambi, Cinthia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina